2013
DOI: 10.1179/0308018813z.00000000052
|View full text |Cite
|
Sign up to set email alerts
|

Flinders Petrie and the Curation of Heads

Abstract: William Matthew Flinders Petrie was a legendary figure in the histories of archaeology and anthropology, recognised for his disciplinebuilding efforts and his contributions to various intellectual paradigms including eugenics and anthropometry. Of lesser renown, however, is the donation of his own head to the collections of the Royal College of Surgeons of England in London. This paper sets that donation in the context of Petrie's lifelong investment in curating other people's heads and in building representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Also, the middle frontal gyrus and the inferior gyrus that were triggered may be engaged in language processing. For example, the large parts of the frontal lobe were triggered when the participants were demanded to read numerous proverbs (Bohrn et al, 2013), poetry (Gao and Guo, 2018), and prose (Zeman et al, 2013). These findings indicated that the process of appreciating Chinese calligraphy involved the perception of the visual words to a minimum extent.…”
Section: Discussionmentioning
confidence: 94%
“…Also, the middle frontal gyrus and the inferior gyrus that were triggered may be engaged in language processing. For example, the large parts of the frontal lobe were triggered when the participants were demanded to read numerous proverbs (Bohrn et al, 2013), poetry (Gao and Guo, 2018), and prose (Zeman et al, 2013). These findings indicated that the process of appreciating Chinese calligraphy involved the perception of the visual words to a minimum extent.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, the activation of MFG, IFG, and middle temporal gyrus (MTG) may also be involved in language processing. For example, large parts of the frontal lobe and MTG were activated when participants were requested to read several proverbs (Bohrn et al, 2013), poetry (Gao & Guo, 2018), and prose (Zeman et al, 2013). These findings indicated that the process of appreciating Chinese calligraphy involved the perception of the visual words.…”
Section: F I G U R Ementioning
confidence: 92%
“…Pearson argued that when there was an irregular curve, a break from the normal measurement, that it showed signs of evolutionary development but this depended on the collection and plotting of large amounts of data (Porter 2004: 239). Like Pearson, Petrie attempted to put in practice a 'visual and graphical' statistical study of race which could be curated for pedagogic purposes (Perry & Challis 2013). Petrie and Pearson had become colleagues at UCL as well as neighbours in Hampstead in 1892 (Porter 2004: 263).…”
Section: Data and Evolutionary Statisticsmentioning
confidence: 99%